Perilaku Komunikasi Otaku dalam Interaksi Sosial (Studi Fenomenologi Pada Anggota Komunitas Jepang Soshonbu Bandung) - Sakinah Biiznilla Yulian; Mohammad Syahriar Sugandi (Program Studi Ilmu Komunikasi, 2019)
Otaku is a term referring to those who fond of Japanese pop culture like anime and manga. Because of some activities, negative views on Otaku developed in the society. This causes Otaku to tend to experience difficulties in interacting with non-Otaku, then they create or join groups or communities that are in accordance with their vision and mission towards Japanese popular culture. With this communities Otaku can interact openly without fear of misunderstanding. This study aims to reveal Otaku’s communication behavior in social interactions. This research method is qualitative research with a phenomenological approach and uses constructivism paradigm. Data collection techniques are carried out by interviews, observation and literatures. Based on the research result revealed that Otaku does some communication behavior in social interaction. In social interaction it produces an associative and dissociative process when Otaku interacting with both other Otaku and non-Otaku. Keywords: Communication Behavior, Otaku, Social Interaction